ANALISIS PENGEMBANGAN AGROWISATA UNTUK KESEJAHTERAAN MASYARAKAT DI KECAMATAN PETANG, KABUPATEN BADUNG - Swastika, I Putu Danu; Sri Budhi, Made Kembar; Urmila Dewi, Made Henny (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.12.TAHUN 2017, 2017)
This study aims to analyze: 1) the influence of government policy on entrepreneurship and infrastructure; 2) the influence of government policy, entrepreneurship and infrastructure on agro-tourism development; 3) the influence of agro-tourism development on community welfare in Petang District, Badung Regency; 4) whether government policies have an indirect effect on the development of agro-tourism through entrepreneurship and infrastructure; 5) whether government policies, entrepreneurship and infrastructure have an indirect effect on the welfare of the people in Petang District, Badung Regency through the development of agro-tourism. Sampling technique with Saturated Sampling involved 91 workers. Data analysis using PLS-SEM. The result of research that government policy have positive and significant influence to entrepreneurship and infrastructure, but have no significant effect on agrotourism development and community welfare. Entrepreneurship has positive and significant impact on agro-tourism development, but has no significant effect on the welfare of the community. Infrastructure has positive and significant impact on agro-tourism development, but has no significant effect on the welfare of the community. Agro-tourism development has positive and significant impact on the welfare of the community.